ЎЗБЕК ХАЛҚ ПОЭТИК ИЖОДИДА ДОСТОНЧИЛИК АНЪАНАЛАРИ (Scientific journal of the Fergana State University, 2023)
In this article information for one of the uzbek oral folk creative work widespread genres  – poem, it’s thematic scale, the message principle, school of story-tellers are given.